Affective Friendship that Constructs Globally Spanning Transnationalism: The Onward Migration of Filipino Workers from South Korea to Canada. (14th March 2016) - Tsujimoto, Toshiko
Abstract: This article explores how affective friendship of migrant Filipino workers constructs transnationalism that overarches different host countries. Following a sequence of 'mobility and sedentariness' through 'multi-sited ethnography' methods, I discuss the affective friendship that emerges out of a specific sociocultural context in Korea, namely activities of the Catholic congregation. I also demonstrate that such friendship is accompanied by onward migration to Canada through the transfer of ties in a new social setting. Moving beyond the duality of home and abroad, this study reveals that migrants' transnationalism exhibits cosmopolitanism through the reconfiguration of their compatriot friendship into globally spanning, multi-local ties.